An unusual presentation of nabothian cyst: a case report - Yelikar, Kanan A. q; Deshpande, Sonali S.; Deshmukh, Shubhangi F.; Pagare, Sanjay B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Nabothian cysts are common gynecologic findings and rarely of clinical significance. They are not problematic unless they are sizeable and present secondary symptoms like in this case. Nabothian cysts are usually associated with chronic cervicitis, an inflammatory condition of cervix, and are harmless and usually disappear on their own. Here we report an interesting case of multiple large nabothian cysts presented with continuous, thin & copious watery discharge, a distressing symptom, mimicking genitourinary fistula. This case is reported for the rarity of symptoms of continuous copious thin watery discharge per vaginum. Very rarely nabothian cyst needs hysterectomy as in our case.